Partial characterization and optimization of protease production from newly isolated Cohnella thermotolerans from Lonar Lake - Tambekar DH; SD, Tambekar (Journal of Research in Biology, 2011)
Lonar Lake, an impact crater located in the Buldhana district of Maharashtra State, India is occupied by saline water and harbors various unidentified, unique haloalkaliphilic bacterial bacillus s